KARAKTERISTIK DAN RANCANG BANGUN EKONOMI ISLAM - Fauziah Sulaiman; Muhtar Lutfi; Rahmawati Muin (Tadayun: Jurnal Hukum Ekonomi Syariah, 2022)
Characteristics in Islamic Economics include the principles of aqidah, morals and law but the building is designed to be derived from the Qur'an, Sunnah, Ijma and Qiyas. Islam does not mean that the principle of equality or the same result is the will of Islamic teachings which is the same as in communism thought. This is contrary to the nature of humans created by Allah SWT. There are differences in the stage of intelligence and other abilities. The purpose of achieving falah in Islamic economics is the realization of pillars, namely basic operational values that appear in Islamic economic principles. Abstrak Karakteristik dalam Ekonomi Islam meliputi asas aqidah, akhlak dan hukum namun bangunannya dirancang agar berasal dari al-Qur’an, Sunnah, Ijma dan Qiyas. Agama Islam tidak memaknai bahwa prinsip sama rata atau hasilnya yang sama itu merupakan kehendak dari ajaran Islam yang sama halnya dalam pemikiran komunisme, hal ini bertentangan dengan fitarhnya manusia yang diciptakan oleh Allah SWT., adanya perbedaan pada tahap kecerdasan dan kemampuan lainnya. Adapun tujuan dari tercapainya falah dalam ekonomi Islam adalah terwujudnya pilar, yaitu nilai-nilai dasar, operasional yang nampak pada prinsip-prinsip ekonomi Islam.